Ideology in U.S. foreign relations : new histories - Nichols, Christopher McKnight; Milne, David, 1976- (New York : Columbia University Press, 2022)
"Ideology drives American foreign policy in ways seen and unseen. Racialized notions of subjecthood and civilization underlay the political revolution of eighteenth-century white colonizers; neoconservatism, neoliberalism, and unilateralism propelled the post-Cold War United States to unleash catastrophe in the Middle East. Ideologies order and explain the world, project the illusion of controllable outcomes, and often explain success and failure. How does the history of U.S. foreign relations appear differently when viewed through the lens of ideology? This book explores the ideological landscape of international relations from the colonial era to the present. Contributors examine ideologies developed to justify-or resist-white settler colonialism and free-trade imperialism, and they discuss the role of nationalism in immigration policy. The book reveals new insights on the role of ideas at the intersection of U.S. foreign and domestic policy and politics. It shows how the ideals coded as "civilization," "freedom," and "democracy" legitimized U.S. military interventions and enabled foreign leaders to turn American power to their benefit. The book traces the ideological struggle over competing visions of democracy and of American democracy's place in the world and in history. It highlights sources beyond the realm of traditional diplomatic history, including nonstate actors and historically marginalized voices. Featuring the foremost specialists as well as rising stars, this book offers a foundational statement on the intellectual history of U.S. foreign policy"--
Introduction: Driving forces : ideas and ideology in the history of U.S. foreign relations / Christopher McKnight Nichols and David Milne -- Indigenous subjecthood and white populism in British America / Matthew Kruer -- American presidents and the ideology of civilization / Benjamin Coates -- Containing the multitudes : nationalism and U.S. foreign policy ideas at the grassroots level / Michaela Hoenicke-Moore -- "Mrs. Sovereign Citizen" : women's international thought and American public culture, 1920-1950 / Katharina Rietzler -- Competing free trade traditions in U.S. foreign policy from the American Revolution to the "American century" / Marc-William Palen -- "The righteous cause" : John Quincy Adams and the limits of American exceptionalism / Nicholas Guyatt -- Antislavery and empire : the early Republican Party confronts the world / Matthew Karp -- The fearful giant : national insecurity and U.S foreign policy / Andrew Preston -- Unilateralism as ideology / Christopher McKnight Nichols -- "For young people" : Protestant missions, geography, and American youth at the end of the nineteenth century / Emily Conroy-Krutz -- Eugenia Charles, the U.S. empire, and military intervention in Grenada / Imaobong Umoren -- I think of myself as an international citizen : Flemmie P. Kittrell's internationalist ideology / Brandy Thomas Wells -- Just war as ideology : a militant ecumenism of Catholics and evangelicals / Ray Haberski Jr. -- Freedom as ideology / Jeremi Suri -- Roads not taken : the Delhi Declaration, Nelson Mandela, Václav Havel, and the lost futures of 1989 / Penny Von Eschen -- "Not just churches" : American Jews, Joint Church Aid, and the Nigeria-Biafra war / Melani McAlister -- Contentious designs : ideology and U.S. immigration policy / Daniel Tichenor -- Capital and immigration in the era of the Civil War / Jay Sexton -- The progressive origins of Project RAND / Daniel Bessner -- Cold War liberals, neoconservatives, and the rediscovery of ideology / Daniel Steinmetz-Jenkins and Michal Franczac -- The galactic Vietnam : technology, modernization, and empire in George Lucas's Star wars / Daniel Immerwahr -- Dual-use ideologies : how science came to be part of the United States' Cold War arsenal / Audra J. Wolfe.
Includes bibliographical references and index
Print version record
JSTOR
Keywords: Ideology -- United States -- History; Democracy; United States -- Foreign relations -- Philosophy; United States -- Politics and government -- Philosophy; Idéologie -- États-Unis -- Histoire; États-Unis -- Politique et gouvernement -- Philosophie; POLITICAL SCIENCE -- International Relations -- General; Democracy; Diplomatic relations -- Philosophy; Ideology; Politics and government; United States; History